Subscribe to our Youtube Channel - https://you.tube/teachoo

Last updated at Dec. 24, 2018 by Teachoo

Transcript

Example 8 Multiply (i) (π₯β4) and (2π₯+3) (π₯ β 4)Γ(2π₯+ 3) = π₯(2π₯+3)β4(2π₯+3) = π₯Γ2π₯+π₯Γ3β4Γ2π₯β 4Γ3 = 2π₯^2+3π₯β8π₯β12 = ππ^πβππβππ Example 8 Multiply (ii) (π₯ β π¦) and (3π₯ +5π¦) (π₯βπ¦)Γ(3π₯+5π¦) = π₯(3π₯+5π¦)βπ¦(3π₯+5π¦) = (π₯Γ3π₯)+(π₯Γ5π¦)β(π¦Γ3π₯)β(π¦Γ5π¦) = 3π₯^2+5π₯π¦β3π¦π₯β5π¦^2 = 3π₯^2+5π₯π¦β3π₯π¦β5π¦^2 = ππ^π+πππβππ^π

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 9 years. He provides courses for Maths and Science at Teachoo.